Antagonistic effects of Talaromyces muroii TM28 against Fusarium crown rot of wheat caused by Fusarium pseudograminearum - Yang, Han; Cui, Shuning; Wei, Yanli; Li, Hongmei; Hu, Jindong; Yang, Kai; Wu, Yuanzheng; Zhao, Zhongjuan; Li, Jishun; Wang, Yilian; Yang, Hetong (Frontiers in Microbiology, 2024)
Fusarium crown rot (FCR) caused by Fusarium pseudograminearum is a serious threat to wheat production worldwide. This study aimed to assess the effects of Talaromyces muroii strain TM28 isolated from root of Panax quinquefolius against F. pseudograminearum. The strain of TM28 inhibited mycelial growth of F. pseudograminearum by 87.8 % at 72 h, its cell free fermentation filtrate had a strong antagonistic effect on mycelial growth and conidial germination of F. pseudograminearum by destroying the integrity of the cell membrane. In the greenhouse, TM28 significantly increased wheat fresh weight and height in the presence of pathogen Fp, it enhanced the antioxidant defense activity and ameliorated the negative effects of F. pseudograminearum, including disease severity and pathogen abundance in the rhizosphere soil, root and stem base of wheat. RNA-seq of F. pseudograminearum under TM28 antagonistic revealed 2823 differentially expressed genes (DEGs). Most DEGs related to cell wall and cell membrane synthesis were significantly downregulated, the culture filtrate of TM28 affected the pathways of fatty acid synthesis, steroid synthesis, glycolysis, and the citrate acid cycle. T. muroii TM28 appears to have significant potential in controlling wheat Fusarium crown rot caused by F. pseudograminearum.